2018
DOI: 10.5005/jp-journals-10078-1237
|View full text |Cite
|
Sign up to set email alerts
|

XEN Gel Stent Early Failure-dye-enhanced Ab-externo Revision

Abstract: The XEN gel stent is an ab-interno minimally invasive glaucoma surgery device that reduces intraocular pressure by creating a subconjunctival drainage pathway. XEN intents to provide a safer and less invasive mean of lowering intraocular pressure. As with any new device, there is still some lack of experience and knowledge concerning efficacy, technique, and complications. We report a novel surgical approach for early bleb failure after XEN implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Ferreira et al 42 reported the first case where Xen early failure (IOP 26mmHg with a thickened non-diffuse bleb despite medical treatment) which was needled with trypan blue injected in the AC prior to the intervention. This case report highlights the advantages of injecting Trypan blue at the time of needling as it helps better assess when the flow is re-established.…”
Section: Efficacy and Safety Of Needling Revisionmentioning
confidence: 99%
“…Ferreira et al 42 reported the first case where Xen early failure (IOP 26mmHg with a thickened non-diffuse bleb despite medical treatment) which was needled with trypan blue injected in the AC prior to the intervention. This case report highlights the advantages of injecting Trypan blue at the time of needling as it helps better assess when the flow is re-established.…”
Section: Efficacy and Safety Of Needling Revisionmentioning
confidence: 99%
“…In human patients, there are a handful of case reports showing bleb-related outflow pathways after tracer injection. 15 – 17 , 19 , 37 Better work has been performed in post-trabeculectomy patients who received intracameral trypan blue injection during cataract surgery showing that greater IOP reduction is seen when there are a greater number of observed pathways. 15 However, simultaneous structural evaluation in prior reports was absent.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Besides its application in the initial surgery, it has also been described as assisting the needling technique for early bleb failure after XEN implantation. 18 Trypan blue is safe for both corneal and trabecular meshwork cells. 11 Moreover, surgeons are already familiar with its use and it is also readily available.…”
Section: Discussionmentioning
confidence: 99%